Folkehelseperspektivet og liberaliseringen av nordisk alkoholpolitikk - Ragnar Hauge (Nordisk Tidsskrift for Kriminalvidenskab)
Nordic alcohol policy has traditionally had as its main target to prevent alcohol abuse and its consequences - drunkenness resulting in aggression, violence and other anti social acts as well as chronic abuse resulting in neglected children and poverty. However, from the late 1960s the focus has gradually changed. Instead there has been an increased preoccupation with the harmful consequences for the users themselves – especially health problems - resulting not only from alcohol abuse but also from more or less moderate drinking.